Hemorrhagic lumbar facet cysts accompanying a spinal subdural hematoma at the same level. (March 2015) - Ikeda, Osamu; Minami, Norihiko; Yamazaki, Masashi; Koda, Masao; Morinaga, Tatsuo
Abstract : Context: We present a rare and interesting case of hemorrhagic lumbar facet cysts accompanying a spinal subdural hematoma at the same level suggesting a possible mechanism by which spinal subdural hematomas can arise. Findings: A 71-year-old man presented with persistent sciatic pain and intermittent claudication. Magnetic resonance imaging demonstrated a multilocular mass lesion that showed high signal intensity in both T1- and T2-weighted images, and was located both inside and outside of the spinal canal. Computed tomographic myelography showed a cap-shaped block of the dural tube at L5 and computed tomography with L5–S facet arthrography demonstrated cystic masses. The patient was diagnosed with lumbar radiculopathy caused by hemorrhagic facet cysts, and then progressed to surgical treatment. Surgery revealed that the cysts contained blood clots, and intraoperative findings that the inside of the dural tube appeared blackish and that the dural tube was tensely ballooned after removal of the cysts led us to explorative durotomy. The durotomy demonstrated concentrated old blood pooling both in the dorsal and ventral subdural space, and these spaces were subsequently drained. After surgery, his sciatic pain and intermittent claudication resolved. There was no evidence of cyst mass recurrence at 2 years of follow-up. Conclusion: We propose a newly described mechanism for the formation of spinal subdural hematomas. We recommend surgeons be alert to epidural lesions causing repeated acute compression of the dural tube, which can cause spinal subdural hematoma, and consider the possible coexistence of these lesions in diagnosis and strategic surgical decisions.